(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In urban planning philosophy, everyone views the city’s future and the priorities concerning these needs. These variants must respect the planning principles. In this study, we tried to solve the problem of the choice of land for urban sprawl, based on several factors to assign the optimal weights to these, and then combined. Our developed prototype GIS/AHP (Geographic Information System/Analytic Hierarchy Process) seeks to find solutions to respect the principles of development but with a justification for the choice of the land base. To show the potential of this prototype, we carried out a diachronic study of the "urban planning and development master plan"(UPDP) of the municipality of El-Bayadh -in its current situation compared to its initial state- in terms of development and the precautions to take before revising it. Through this research, we have seen some dysfunctions in the combination of development rules to this end; we combined the geographic information system with the multi-criteria analysis to take into account parameters concerning land management, like vegetative cover lithology; constraints to be met such as the flood hazard map; and other legislative criteria such as legal ownership. The combined GIS / AHP solution has advantages in land choice according to the maximum parameters, controlling the whole municipal territory by knowing all its characteristics and widening the choice interval in terms of the land plot.